Optimum dose of olsalazine for maintaining remission in ulcerative colitis. - Travis, S; Tysk, C; de Silva, H; Sandberg-Gertzén, H; Jewell, D; Järnerot, G (1994)
To evaluate the optimum dose of olsalazine for maintaining remission in ulcerative colitis, 198 patients in remission for more than three months were randomly assigned to receive 0.5 g, 1.0 g, or 2.0 g/day for 12 months. A dose-ranging effect was detected in the per protocol analysis, with remission rates of 60% (0.5 g), 70% (1.0 g), and 78% (2.0 g) (p = 0.03, trend in proportions). The higher dose was most effective in patients with proctitis (90% remission on 2 g/day, p = 0.03) or those in remission for less than 12 months before the trial (88% remission on 2 g/day, p = 0.0006). There was little dose-ranging effect in patients with extensive colitis or those in remission for more than 12 months. Diarrhoea necessitated treatment withdrawal in 12%. The optimal dose of olsalazine for maintaining remission in ulcerative colitis is 1 g/day. For patients with proctitis or recent relapse, 2 g/day may be preferable, although the dose seems to be less important in patients with more extensive disease or those in long term remission.